PEMBELAJARAN BERBASIS MUSIKAL ‘PETUALANGAN SI TETES AIR’ SEBAGAI INOVASI MEDIA SIKLUS AIR DI SEKOLAH DASAR - Nabiilah Damayanti; Rini Wulandari; Khulaimata Zalfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study develops a musical learning medium titled “Petualangan Si Tetes Air” to support elementary school students’ understanding of the water cycle within the context of IPA (Integrated Science and Social Studies). Using a qualitative descriptive approach with the ADDIE model, this study integrates scientific concepts into simple, engaging, and easy-to-remember song lyrics. Data were collected through literature review and Focus Group Discussion (FGD). The results indicate that this medium can simplify abstract concepts such as evaporation, condensation, and precipitation while enhancing students’ memory retention and learning motivation through rhythm and repetition. Although not yet implemented directly in classroom settings, supporting literature suggests its strong potential effectiveness. Therefore, this musical medium offers a practical, innovative, and creative alternative for science learning in elementary education.